2006
DOI: 10.4049/jimmunol.177.9.6018
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Cross-Dressed with Peptide MHC Class I Complexes Prime CD8+ T Cells

Abstract: The activation of naive CD8+ T cells has been attributed to two mechanisms: cross-priming and direct priming. Cross-priming and direct priming differ in the source of Ag and in the cell that presents the Ag to the responding CD8+ T cells. In cross-priming, exogenous Ag is acquired by professional APCs, such as dendritic cells (DC), which process the Ag into peptides that are subsequently presented. In direct priming, the APCs, which may or may not be DC, synthesize and process the Ag and present it themselves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 37 publications
3
119
0
Order By: Relevance
“…Migration of these DCs to the LN may induce the activation of CD8 + T cells by direct Ag presentation as well as through cross-presentation by LN resident CD8a + DCs (27,28). Nonetheless, at the same time our data may suggest that Ag transfer from migratory CD103 + DCs or CD11b + DCs may occur through the donation of intact MHC class I:viral peptide complexes to resident uninfected DCs, even if en route the DC undergo virus-induced apoptosis or cytolysis (13). Similarly, within the spleen, it could be envisaged that blood-borne viral Ag captured by splenic marginal zone macrophages or viral Ag acquired by CD8a + DCs located in the outer marginal zone (29,30) may be donated as MHC class I:viral peptide complexes to spleen resident CD8a 2 DCs unable to cross-present viral Ag directly (31).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Migration of these DCs to the LN may induce the activation of CD8 + T cells by direct Ag presentation as well as through cross-presentation by LN resident CD8a + DCs (27,28). Nonetheless, at the same time our data may suggest that Ag transfer from migratory CD103 + DCs or CD11b + DCs may occur through the donation of intact MHC class I:viral peptide complexes to resident uninfected DCs, even if en route the DC undergo virus-induced apoptosis or cytolysis (13). Similarly, within the spleen, it could be envisaged that blood-borne viral Ag captured by splenic marginal zone macrophages or viral Ag acquired by CD8a + DCs located in the outer marginal zone (29,30) may be donated as MHC class I:viral peptide complexes to spleen resident CD8a 2 DCs unable to cross-present viral Ag directly (31).…”
Section: Discussionmentioning
confidence: 46%
“…Recently, a third mechanism known as cross-dressing has been proposed to contribute to antiviral immunity, whereby an uninfected APC acquires pre-existing MHC class I:peptide molecules from a virus-infected cell (9)(10)(11). In support of such a role, we, and others, have shown that MHC class I:peptide complexes can be acquired by immature and mature dendritic cells (DCs) both in vitro and in vivo (10)(11)(12)(13)(14)(15). Furthermore, the transferred MHC:OVA peptide complexes were functional in that they stimulated OVA-specific CD8 + T cell proliferation and IL-2 production (9).…”
Section: Uring the Immune Response To A Virus Infection It Ismentioning
confidence: 98%
“…DCs can acquire pMHC complexes after direct contact with dead Ag-expressing cells (41), and DCs cross-dressed with pMHC complexes derived from monocytes that phagocytosed Ags from virus-infected dead cells could elicit antiviral CD8 + T cell responses (42). More recently, an elegant study demonstrated the in vivo significance of cross-dressed DCs in the activation of memory CD8 + T cells against a viral infection (43).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we also found that phosphatidylserine was translocated to the outer layer of the membrane of MPs, the marker of apoptosis (Figure 4c). Given DCs acquiring antigens via multiple ways, [25][26][27][28] two possibilities were speculated here to further dissect how MPs transferred Lm antigenicity to DCs: (i) DCs use membrane fusion strategy to directly acquire Lm antigen peptide-MHC complexes from MPs; or (ii) DCs internalize MPs, process Lm …”
Section: Macrophages Participate In DC Presenting Lm Antigens In Vitromentioning
confidence: 99%